Effect of CYP2D6 and ABCB1 polymorphisms on pharmacokinetics and efficacy of aripiprazole in pediatric tic disorders - Yingying Xin; Liuliu Gao; Sichan Li; Jun Wang; Chen Chen; Yali Tuo; Gang Nie; Ruizhen Li; Dan Sun; Yongli Fu; Yang Wang; Zhisheng Liu (BMC Pediatrics)
Abstract Background Aripiprazole (ARI) is the first-line treatment for tic disorders (TD). Cytochrome P450(CYP)2D6 (CYP2D6) and ATP-binding cassette, sub-family B, member 1 (ABCB1) transporter are involved in the metabolism of ARI. However, whether CYP2D6 and ABCB1 genetic polymorphisms influence clinical efficacy and pharmacokinetics of ARI remains unclear. Methods CYP2D6 and ABCB1 genotyping were performed. Pharmacokinetic parameters of ARI and its metabolite dehydroaripiprazole (DARI) were derived using a previously established population pharmacokinetic model. Drug response after ARI administration was evaluated based on reduction rate of Yale Global Tic Severity Scale score (YGTSS). Results Steady-state DARI/ARI metabolic ratios (MRs) of AUC0 − t, Cmin and Cmax were significantly associated with CYP2D6 rs1135840, CYP2D6 rs5030865, CYP2D6 rs1058164, CYP2D6 rs28371702, CYP2D6 rs1065852 and CYP2D6 rs1080989. The clearance (CL) of ARI was influenced by CYP2D6 rs1135840, CYP2D6 rs5030865, and CYP2D6 rs1080989. CYP2D6 rs16947, CYP2D6 rs29001518 and CYP2D6 rs1080985 were correlated with the CL of DARI. The CYP2D6 rs5030865 polymorphism was associated with volume of distribution (V) of DARI. The ABCB1 C3435T (rs1045642) polymorphism influenced the V of ARI. CYP2D6 rs1065852 and CYP2D6 rs1080989 were significantly associated with drug response of ARI. Conclusion Pharmacokinetic parameters of ARI were correlated with CYP2D6 polymorphisms. CYP2D6 genotyping was recommended in ARI therapy. Further researches are required to elucidate the role of ABCB1 polymorphisms in ARI metabolism.